2020
DOI: 10.1002/ps.6104
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining induced heat shock protein 70 confers biological thermotolerance in a high‐temperature adapted predatory mite Neoseiulus barkeri (Hughes)

Abstract: BACKGROUND In fluctuating climatic environments, heat acclimation in predatory mites is a superior adaptation strategy for effective agricultural pest management and can be used to enhance the abilities critical in biological control efficiency. We investigated the regulatory mechanism governing the remarkable plastic response of thermotolerance in a high‐temperature adapted strain (HTAS) and discerned the differences in the defensive reactions between the HTAS and the conventional strain (CS) in the predatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Our study showed that the expression of the PpHSP27 , PpHSP60 , and PpHSC70 genes increased significantly with increasing stress temperature and stress duration in all treatment groups. This is consistent with the results of Agasicles hygrophila , Neoseiulus barkeri , and Scylla paramamosain [ 46 , 47 , 48 ]. From this, we hypothesized that these three HSP genes may help P. pseudoannulata to resist heat stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that the expression of the PpHSP27 , PpHSP60 , and PpHSC70 genes increased significantly with increasing stress temperature and stress duration in all treatment groups. This is consistent with the results of Agasicles hygrophila , Neoseiulus barkeri , and Scylla paramamosain [ 46 , 47 , 48 ]. From this, we hypothesized that these three HSP genes may help P. pseudoannulata to resist heat stress.…”
Section: Discussionsupporting
confidence: 92%
“…A similar phenomenon was observed in B. tabaci , and D. melanogaster [ 22 , 23 ]; however, the exact cause of this phenomenon is not clear at this time and further studies are needed. The study on N. barkeri showed that the protein level of HSP70-1 was positively correlated with the expression of NbHSP70-1 , and the overexpression of Nb HSP70 protein in Escherichia coli ( E. coli ) enhanced the high temperature tolerance of E. coli [ 47 ]. Overexpression of HSP40 from Cydia pomonell in E. coli enhanced the high temperature tolerance of E. coli [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with other studies, the findings suggest that on a short time scale (a few hours) the damage caused by high-extreme temperatures can be compensated or repaired during milder thermal periods (Bai et al, 2019;Ma et al, 2018). However, when the stress is prolonged for several days, different physiological mechanisms can occur, allowing acclimation to warmer conditions, e.g., accumulation of heat shock proteins and metabolic compensation (le Lann et al, 2011;Pazouki et al, 2016;Stanton-Geddes et al, 2016;Tian et al, 2021). Moreover, the biotic context in which species develop mediates the thermal performance of the focal species having rippling effects on community dynamics.…”
Section: Conclusion and Future Perspectivessupporting
confidence: 88%
“…Molecular tools such as omic techniques can give a complete phenotypic and genotypic picture of an individual at a given time in a given environment, and their use significantly improves the understanding of physiological effects of environmental variables on phenotypic plasticity (Hayward, 2014). Among the different physiological responses to temperature stress that were identified (recently reviewed in González-Tokman et al, (2020), HSPs have received most attention (Feder & Hofmann, 1999;Ju et al, 2011;King & MacRae, 2015;Tian et al, 2021). HSPs are molecular chaperone proteins protecting proteins and cells against the destabilising effect of high temperature, thus playing an important role in insect heat tolerance, rapid hardening, and developmental acclimation (Feder & Hofmann, 1999;Sørensen et al, 2003).…”
Section: Physiological Effects Of Fluctuating Thermal Regimesmentioning
confidence: 99%
“…One study showed that in Pteromalus puparu , a significant upregulation of Pphsc70 expression was caused by heat treatment; however, the continued exposure to thermal stress and a return to normal temperature caused a gradual downregulation to even lower levels of expression than those of control pupae [ 42 ]. Furthermore, results in a study on the mite Neoseiulus barkeri revealed that the expression of two NbHsp70s was significantly elevated at 42 °C but then sharply decreased after 4 h of heat treatment [ 43 ]. In this study, our results revealed that Hsp70s upregulation at 39 °C of heat treatment reached peak levels within 30 min in diapause pupae, but was downregulated when the incubation time was prolonged to 1–2 h with recovery after 4 h in WD pupae ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%